Cecal bascule – An unusual cause of intestinal obstruction: A case report. (May 2021) - Shakeel, S. Areesha; Zaman, Junaid; Haroon, Hamza
Highlights: Cecal bascule is rare. Case of Elderly female with cecal bascule. Ceceomy + ileo-cecal anastomosis was done. Should consider cecal bascule in acute abdomen. Abstract: Introduction: Cecal bascule is a rare type of cecal volvulus occurring in the elderly population with a male predominance. It is a condition where the cecum folds upward upon itself. Importance: There are only a handful of case reports published about cecal bascule. This is the first case being reported from Pakistan. Case presentation: A 68 year old female, known hypertensive and osteoporosis presented in the ER with complaints of vomiting, abdominal distension and absolute constipation. Radiology was non-diagnostic. She was treated with cecectomy and anastomosis. Post operatively she developed ileus for which was managed. She was subsequently discharged at 8th day post op. Clinical discussion: The management of cecal bascule is always surgery with predilection towards cecopexy or cecetomy to prevent recurrence. This manuscript is as per the SCARE case report checklist [1 ].